(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Application of information technology (IT) in Libraries has change the concept of information processing and its dissemination. With the introduction of micro information technologies the Traditional System of management was replaced by the modem System information technology. Such IT application was compelled by various factors and there are many areas of computerization in libraries services. This resulted electronic information availability for the networked or automated libraries with this new system library collection may be in a digital or electronic form. The whole concept of library and its services have been changed due to the advent of new electronic information services and use of internet facilities.